A Study of Relationship between Diabetic Nephropathy and Lipid Profile, Hs-CRP, Blood Sugar and Blood Pressure among Patients. - Uppal, Arpan; Kapoor, Utkarsh (Journal of Neonatal Surgery, 2025)
Diabetes mellitus (DM) has emerged as a significant worldwide health issue. One of the most significant long-term microvascular consequences of diabetes mellitus (DM) is type 2 diabetic nephropathy (T2DN), which is a major contributor to end-stage renal disease (ESRD) at the global level. Diabetic nephropathy is a mild inflammatory condition which is linked with many other types of diseases and can cause a lot of other diseases to generate in our body. So, the objective of this study is to find the degree of correlation between Diabetic Nephropathy and Lipid Profile, Hs-CRP, Blood Sugar and Blood Pressure among Patients. For this purpose, two group of patients were taken; one as an experimental group and one as a controlled group. A total of 68 patients were taken as sample for both the groups. Lipid Profile, Hs-CRP, Blood Sugar and Blood Pressure were assessed in both the groups. The data was analysed using SPSS version 16.0. Mean, SD, Chi-square test, Unpaired t-test were calculated to find the relationship between Diabetic Nephropathy and Lipid Profile, Hs-CRP, Blood Sugar and Blood Pressure among Patients. The study concluded that there is a high degree of correlation between the Diabetic Nephropathy and Lipid Profile, Hs-CRP, Blood Sugar and Blood Pressure among Patients.